1keV デンシ ノ コウカ ニ ヨル デンリソウ ノ セイセイ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 上山, 弘; カミヤマ, ヒロシ; KAMIYAMA, Hiroshi (国立極地研究所, 1972)
P(論文) This short note describes the ionospheric effect of 1 keV-electrons incoming possibly from the magnetotail. The rate of the ionization produced through the impact of these electrons is calculated as a function of altitude, and the maximum is found to be 1.85 × 10^3 cm^<-3> s^<-1> at the altitude of 154 km for the isotropic incidence of a flux of 10^8 cm^<-2> s^<-1> ster^<-1>. The height profile of the electron density in the equilibrium shows the minor maximum of 8.5 × 10^4 cm^<-3> at the level slightly above the level of the maximum production rate and the major F2 peak of 2.3 × 10^5 cm^<-3> at about 300km. The lifetime of the ionization is estimated to be about 43 minutes for the F2 peak, while the lower layer will fade out shortly after the ceasing of the electron precipitation. departmental bulletin paper